Mental models of the protein shift: exploring consumers’ perceptions of the transition - Van den Boom, Lieke; Van den Broek, Karlijn; Kroese, Floor M.; Moors, Ellen H. M.; de Ridder, Denise T. D. (Appetite, 2023)
The protein transition is one of today's major societal challenges to mitigate climate change. To support lasting consumer engagement, it has been suggested to look into consumers' understanding of the protein transition to identify barriers that go beyond the practical issues of changing one's diet. The current study explored consumers' mental models of how the transition unfolds to examine which factors consumers perceive as important drivers of the transition. With a fixed set of factors and actors identified with a questionnaire, Dutch consumers (N = 214) mapped their mental models. The content and structure of the mental models were analyzed with a focus on how consumers perceive their own role. Animal well-being and environmental concerns were most often included as important drivers. The findings showed a lack of consensus about which actor(s) drive the transition (i.e., none of the actors were included by a majority of the participants). This diffusion of responsibility may be a barrier for consumers to act. Moreover, the relative simplicity of the observed mental models suggests that consumers do not yet employ systems thinking. A systems thinking mindset may help consumers understand how the system behind the transition works and how their individual contributions matter. Two avenues to encourage consumer engagement were identified: 1) emphasizing the responsibility of different actors and what consumers can contribute, and 2) encouraging a systems thinking mindset.
Online verfügbar 8. Mai 2023, Artikelversion 20. Mai 2023
Gesehen am 20.07.2023